I need help on these 2
I need help on these 2 - 1

Answers

Answer 1
Answer: 8)
6(2+2p)=-8(4-p)
12+12p=-32+8p
-8p -8p
12+4p=-32
-12 -12
4p=-44
/4 /4
p=-11

*whatever you do to one side of the equation you have to do to the other

Related Questions

diagram 7(i) shows a square with area of 64cm² formed using a string.The string is cut to form another two congruent rectangles with length 5 cm, as shown in diagram 7(ii).Calculate the area , one of the rectangles.If u guys can help me solve this, u guys really save my life.I need to submit tomorrow morning.​
Which of the following equations describe the line shown below?Check all that apply
How many positive integers less than 25 can be formed by using the digits 1,2 and 3
Liam bought 34of a pound of strawberries. He used the strawberries to make 6 smoothies. If each smoothie had the same amount of strawberries, how many pounds of strawberries did Liam use to make 1 smoothie?One-fourth poundOne-eighth poundOne-sixth poundStartFraction 1 Over 12 EndFraction pound
How old would someone be if they were born on the 30th october 1992 ????

How do I expand this?    3(2y-5)

Answers

Answer:

Given the expression 3 (2y-5)                   ......[1]

Distributive property of multiplication states that when a number is multiplied by the sum of two numbers, then the  first number can be distributed to both of those numbers and multiplied by each of them separately. i.e,

a \cdot (b+c) =a\cdot b +a \cdot c

then, by using distributive property in equation [1]

3(2y-5) = 3 \cdot 2y - 3\cdot 5

                  = 6y-15

Therefore, the expanded form of 3(2y-5) is; 6y-15

3\cdot(2y-5)=3\cdot2y-3\cdot5=6y-15

Answer has to be in units

Answers

It's a deal.  Give me a question, and I'll give you an answer in units.
Yep I'll try to answer to if you would give us something to answer..

Simplify 4 times the 4th root of 48.

Answers

For the answer to the question above asking to Simplify 4 times the 4th root of 48.
√48
=√16*3
=√2^4*3
=2√3
=2 times the 4th root of 3

I hope my answer helped you with your problem. Have a nice day! Feel free to ask more questions.

F (a)=2a^2-16a+32
For which 'a' is this equation 0?

Answers

if xy=0 assume that at leas 1 is zero
set it to zero

0=2a^2-16a+32
undistribute 2
0=2(a^2-8a+16)
2*0=0 so assume
a^2-8a+16=0
factor
(a-4)(a-4)=0
set to zero
a-4=0
a=4


when a=4, equation equals zero

What value is equivalent to 13 − 2(1 − 15) ÷ 4?A) -38.5
B) -26
C) 7.25
D) 20

Answers

Answer:

D 20

Step-by-step explanation:

13 − 2(1 − 15) ÷ 4

PEMDAS says parentheses first

13 − 2(-14) ÷ 4

Then multiply and divide from left to right

13 +28 ÷4

13+7

Then add and subtract

20

Answer:

D. 20

Step-by-step explanation:

Follow PEMDAS

- Hope that helps! Please let me know if you need further explanation.

What is an equation of the line that passes through the points (-5, 1)(−5,1) and (5, 3)(5,3)?

Answers

Answer:

x=-5 i think

Step-by-step explanation: